2021
DOI: 10.36740/wlek202104135
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiovascular Risk in Patients With Type 2 Diabetes Mellitus and Associated Obesity and Ways of Its Correction

Abstract: The aim: To analyze and calculate CVR in patients with T2DM and concomitant obesity. Materials and methods: The selection of patients was carried out based on the Uzhhorod District Clinical Hospital, in the period from November 2016 to January 2020. All patients were divided into 3 groups: 1 (n=93) with T2DM and concomitant obesity, 2 (n=87) with T2DM, 3 (n=39) with obesity. The treatment period lasted 1 year and included dosed exercise for at least 30 minutes per day and dietary recommendations. Patients in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(27 reference statements)
0
1
0
1
Order By: Relevance
“…This recommendation is consistent with the findings of this review as only those exercising for more than 30 min demonstrated an improvement in cognitive impairment. An increasing number of studies report that exercise lasting for at least 30 min plays an essential role in reducing cardiovascular risk factors (Griadil et al, 2021; Ting et al, 2015; Warburton & Bredin, 2016), which have been linked with cognitive impairment (Maasakkers et al, 2020). Additionally, a review found that cognitive performance could be immediately improved after a single bout of exercise at least for 30 min (Chang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is consistent with the findings of this review as only those exercising for more than 30 min demonstrated an improvement in cognitive impairment. An increasing number of studies report that exercise lasting for at least 30 min plays an essential role in reducing cardiovascular risk factors (Griadil et al, 2021; Ting et al, 2015; Warburton & Bredin, 2016), which have been linked with cognitive impairment (Maasakkers et al, 2020). Additionally, a review found that cognitive performance could be immediately improved after a single bout of exercise at least for 30 min (Chang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A gravidade mostrou-se, ainda, associada significativamente a todas as covariáveis inseridas no modelo da regressão. O prognóstico da gravidade da associação entre DM e COVID-19 tem várias explicações: por ser uma condição crônica que altera as funções metabólicas, o paciente diabético possui resposta imunológica ineficaz frente às infecções, tornando o organismo inapto a proteger-se contra dados fisio-Garces TS, Sousa GJB, Cestari VRF, Mattos SM, Florêncio RS, Pereira MLD, et al lógicos (15) , além disso, o diabetes amplia o risco de fibrose pulmonar e diminui a função respiratória (16) , sendo considerado um promotor da vulnerabilidade cardiovascular (17) .…”
Section: Discussionunclassified